1981
DOI: 10.1111/j.1432-1033.1981.tb05089.x
|View full text |Cite
|
Sign up to set email alerts
|

Purification and Some Properties of NAD‐Glycohydrolase from Conidia of Neurospora crassa

Abstract: NAD‐glycohydrolase from conidia of Neurospora crassa was purified by affinity chromatography, using 4‐methylnicotinamide adenine dinucleotide as ligand immobilized onto Sepharose through a hydrophilic spacer arm. The pure enzyme is a glycoprotein with an isoelectric point of 5.5 and a molecular weight of 33000 as determined by sodium dodecylsulphate gel electrophoresis. The specific activity is the highest so far found for NAD‐glycohydrolases and in various aspects the enzyme is different from that isolated fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

1985
1985
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 28 publications
1
3
0
Order By: Relevance
“…1E). This is in line with studies that showed glycosylation of N. crassa NADase and could explain the discrepancy between the observed and theoretical molecular masses 13 . A predicted N-terminal secretory signal peptide in the A. fumigatus protein was confirmed by LC-MS/MS (highlighted in blue in Fig.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…1E). This is in line with studies that showed glycosylation of N. crassa NADase and could explain the discrepancy between the observed and theoretical molecular masses 13 . A predicted N-terminal secretory signal peptide in the A. fumigatus protein was confirmed by LC-MS/MS (highlighted in blue in Fig.…”
Section: Resultssupporting
confidence: 92%
“…Identification of fungal surface NADases. Since conidia from N. crassa have been known to exhibit NADase activity, we tested whether conidia from the human opportunistic pathogen A. fumigatus may have a similar activity 13 . Using the fluorescent NAD + analogue nicotinamide 1, N6-ethenoadenine dinucleotide (εNAD + ) we detected robust cleavage on the surface of A. fumigatus conidia from the strain CEA17ΔakuB, indicating the presence of one or more NADases (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This V max is 10 2 -to 10 4 -fold higher than the minor NADase activity reported in certain other bacterial ARTases (15,(39)(40)(41). It is also a higher activity than that reported for NADases purified from rabbit erythrocytes and Bungarus fasciatus venom, while lower than the activity of NADases purified from N. crassa and streptococci (12,25,35,58). Thus, the specific NADase activity of HvnA lies within a range reported for NADases and would be exceptionally high for the background NADase activity of an ARTase.…”
Section: Vol 183 2001mentioning
confidence: 60%